Bibliometric analysis and trends: an application in senior tourism - Pestana, M. H.; Parreira, A.; Wang,W. - C. (International Journal of Business and Economics, 2019)
This study applies bibliometric analysis to senior tourism research from 1998 to 2017, identifies its intellectual structure, emerging trends, and future research opportunities. A detailed search of documents collated from Web-of-Science and Scopus was implemented and analyzed through CiteSpace. The results reveal a slowly increasing growth of research with six main areas of research. The network of journals shows a core peripheral structure with Tourism Management ranked first. Among countries’ publications, the United States leads in volume. The identification of structural holes, the keyword analysis and development of emerging tendencies highlights priorities in senior tourism pointing to new opportunities for research. This study is differentiated from others by its temporal and dynamic analysis of the last two decades, utilizing CiteSpace for a co-citation and co-occurrence network analysis. As a result, the researchers and the hospitality sector were equipped with new exploration tools.